2020
DOI: 10.1038/s41422-020-0378-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cell lineage differentiation during hepatogenesis in humans and mice at the single-cell transcriptome level

Abstract: During embryogenesis, the liver is the site of hepatogenesis and hematopoiesis and contains many cell lineages derived from the endoderm and mesoderm. However, the characteristics and developmental programs of many of these cell lineages remain unclear, especially in humans. Here, we performed single-cell RNA sequencing of whole human and mouse fetal livers throughout development. We identified four cell lineage families of endoderm-derived, erythroid, non-erythroid hematopoietic, and mesoderm-derived non-hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 92 publications
5
76
0
Order By: Relevance
“…However, Wang and co-workers found the opposite results. They found that, in both humans and mice, the proliferation rate of hepatoblasts/hepatocytes decreased throughout development ( Wang et al, 2020 ). These differences between studies may be related to both the selection of embryonic stage and the methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Wang and co-workers found the opposite results. They found that, in both humans and mice, the proliferation rate of hepatoblasts/hepatocytes decreased throughout development ( Wang et al, 2020 ). These differences between studies may be related to both the selection of embryonic stage and the methods.…”
Section: Discussionmentioning
confidence: 99%
“…The liver consists of greater than 20 cell types, including hepatocytes, liver endothelial cells, biliary ductal cells (cholangiocytes), mesothelial cells, Kupffer cells, and various circulatory immune cells, which are all organized to form the foundation for liver functions, including glycolytic and urea metabolism, immune responses, and drug detoxification ( Wang et al, 2020 ). In the development of human fetus, liver is an essential hemopoietic organ.…”
Section: Introductionmentioning
confidence: 99%
“…The specification of hepatoblasts toward hepatocytes has shown to be a default‐directed progressive process in which the transition is characterized by gradual changes in gene expression. However, this is not the case for cholangiocytes which the transition requires regulated signaling and also requires to escape from the default‐directed hepatoblast‐hepatocyte transition (Wang et al, 2020). Differentiation of hepatoblasts into cholangiocytes is promoted by FGF, BMP, and dominantly TGF‐β (through notch signaling) gradients, whereas other signaling molecules such as HGF, OSM, and glucocorticoids induce hepatocyte differentiation (Shin and Monga, 2013; Snykers, De Kock, Rogiers, & Vanhaecke, 2009).…”
Section: Signaling Moleculesmentioning
confidence: 99%
“…Although the main phases of liver regeneration were discussed separately in previous sections, mechanistically, numerous investigations have indicated a complex array of interactive signaling factors between these phases, which shows an orchestrated operation of these phases with highly overlapping functions. During early hepatogenesis where the differentiation of progenitor cells toward specified hepatocytes is pursued, not only the proliferation of progenitor cells along with progressive gene specialization (toward hepatocytes) occurs, but also, simultaneously, the proliferation of highly specified hepatocytes is followed where a mixture of proliferating hepatoblast and hepatocytes is detectable in the developing tissue (Butler, Hoffman, Smibert, Papalexi, & Satija, 2018; Michalopoulos & DeFrances, 1997; Wang et al, 2020). In fact, as the tissue development proceeds, the ratio of hepatoblast/hepatocytes is decreased until the time in which the regeneration is further followed only by hepatocyte proliferation (Butler et al, 2018; Wang et al, 2020).…”
Section: Regeneration Time Framementioning
confidence: 99%
See 1 more Smart Citation